Pseudomonas aeruginosa Polynucleotide Phosphorylase Contributes to Ciprofloxacin Resistance by Regulating PrtR - Fan, Zheng; Chen, Hao; Li, Mei; Pan, Xiaolei; Fu, Weixin; Ren, Huan; Chen, Ronghao; Bai, Fang; Jin, Yongxin; Cheng, Zhihui; Jin, Shouguang; Wu, Weihui (Frontiers in Microbiology, 2019)
Pseudomonas aeruginosa is an opportunistic bacterial pathogen that causes various acute and chronic infections. It is intrinsically resistant to a variety of antibiotics. However, production of pyocins during SOS response sensitizes P. aeruginosa to quinolone antibiotics by inducing cell lysis. The polynucleotide phosphorylase (PNPase) is a conserved phosphate-dependent 3’–5’ exonuclease that plays an important role in bacterial response to environmental stresses and pathogenesis by influencing mRNA and small RNA decay. Previously, we demonstrated that PNPase controls the type III and type VI secretion systems in P. aeruginosa. In this study, we found that mutation of the PNPase coding gene (pnp) increased the bacterial resistance to ciprofloxacin. Gene expression analyses revealed that the expression of pyocin biosynthesis genes was decreased in the pnp mutant. PrtR, a negative regulator of pyocin biosynthesis genes, was up regulated in the pnp mutant. We further demonstrate that PNPase represses the expression of PrtR on the post-transcriptional level. A fragment containing 43 nucleotides of the 5’ untranslated region was found to be involved in the PNPase mediated regulation of PrtR. Overall, our results reveled a novel layer of regulation on the pyocin biosynthesis by the PNPase in P. aeruginosa.